2014
DOI: 10.1002/app.41028
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel twin‐tailed hydrophobically associated copolymers and their applications to Cr(III) removal from aqueous solutions

Abstract: Water pollution is one of the most serious environmental problems facing society. The objective of this study was to provide an efficient and inexpensive way of removing Cr(III) from polluted water. Novel twin‐tailed hydrophobically associating copolymers (PAAD) were prepared by micellar copolymerization of acrylamide (AM) and sodium 2‐acrylamido‐2‐methylpropane sulfonate with N,N‐dibutylmethacrylamide in an aqueous solution. The PAAD series, comprising copolymers of different molecular weights (ranged from 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…This is further evidence of successful modification of the polymers . For HMWSP the maximum concentration that is typically employed is 5 mol % . However, we modified polymers to 20 mol % to try to react all of the carboxylate groups to generate copolymers containing acrylamide and the functionalized group.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…This is further evidence of successful modification of the polymers . For HMWSP the maximum concentration that is typically employed is 5 mol % . However, we modified polymers to 20 mol % to try to react all of the carboxylate groups to generate copolymers containing acrylamide and the functionalized group.…”
Section: Resultsmentioning
confidence: 82%
“…Synthetic water‐soluble polymers have been used for a number of years as viscosity enhancers in a broad number of industrial applications including paint formulations, foods, water purification, pharmaceuticals, cosmetics, drilling fluids, enhanced oil recovery, hydraulic fracturing and drag reducing agents . Polymers based on acrylamide (PAM) are the most extensively studied group of synthetic water‐soluble polymers so they are commercially available in large quantities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, polyacrylamide-based polymers are sensitive to mechanical degradation in environments with high temperature, shear, or in the presence of electrolytes [2], making a great effort necessary for the synthesis of their derivatives, aiming to overcome this limitation, with emphasis on the known hydrophobically modified watersoluble polymers (HMWSP). HMWSP are amphiphilic copolymers consisting of a large hydrophilic portion in the chain and a small hydrophobic portion, with an incorporation limit of less than 5 mol% [3]. The hydrophobic groups incorporated into the macromolecule can promote a significant increase in viscosity, as they tend to associate, pushing away water molecules and generating intra or intermolecular aggregates in solution [2].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their properties in aqueous solution, which are caused by the interaction of intramolecular and intermolecular chains between the hydrophobic groups, they are widely used in oil and gas development, engineering materials, industrial coatings, sewage sludge, and drug controlled release [1,2], but their properties and structures can be greatly affected by salinity and temperature. Most studies have only revealed the effect of salinity on the viscosity of polymer solutions, but the effects on the microstructure and other rheological properties have rarely been reported [3,4].…”
Section: Introductionmentioning
confidence: 99%